2013
DOI: 10.3126/jaim.v2i2.8777
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection, its correlation with gastroduodenal diseases and the incidence of gastric cancer in Nepal

Abstract: Background and aims: The Helicobacter pylori (H. pylori) prevalence in Asian countries is highly variable, with higher seroprevalence shown in the previous studies of developing Asian countries. We aimed to determine the current H. pylori prevalence, correlate with gastroduodenal diseases and study gastric cancer incidence in Nepal. Methods: Among 3357 patients referred for endoscopy, 2820 eligible patients underwent upper gastrointestinal endoscopy with biopsy; H. pylori was considered positive when either of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
10
2
Order By: Relevance
“…Demographically, Gastric cancer was found commonly in 61-70 years, and in Gurung community (Janajati-Hill in our category) in a study by Ghosh et al 13,23 In our series, though Janajatis comprise 37% of the population, they accounted for 42% of cases of gastric carcinomas and around 65% of the patients were concentrated on 20 districts (25% of the geography). Since these patients belong to the hilly region of the country, it limits their accessibility to health care facilities and devoid them of the benefit of early diagnosis and cure.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Demographically, Gastric cancer was found commonly in 61-70 years, and in Gurung community (Janajati-Hill in our category) in a study by Ghosh et al 13,23 In our series, though Janajatis comprise 37% of the population, they accounted for 42% of cases of gastric carcinomas and around 65% of the patients were concentrated on 20 districts (25% of the geography). Since these patients belong to the hilly region of the country, it limits their accessibility to health care facilities and devoid them of the benefit of early diagnosis and cure.…”
Section: Discussionsupporting
confidence: 46%
“…3 In a study done in Kaski district of Nepal, it was found to be 3.3 per 100000. 13 In Nepal the age standardized death rate from gastric cancer for 2010 is 8.38 and Nepal ranks 71 st in the world rank in gastric cancer. 14 Nepal is a developing country with limited recourses and the difficult terrain limits accessibility of health care facility by the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the prevalence of gastric cancer among patients undergoing UGI endoscopies was 2.4%. In a previous Nepalese study from this region in 2013 comprising of 2820 endoscopies by Shrestha et al 6 , gastric carcinoma prevalence was reported to be 1.8%. The prevalence or detection of gastric cancer may be rising every year in this region.…”
Section: Discussionmentioning
confidence: 89%
“…Females are more frequently affected by cancer than males [ 28 ]. However, age-standardized annual gastric cancer has a prevalence of 3.3 in 100,000 [ 29 ] and a male-female ratio of 2.8:1 [ 23 ]. Women of advanced age have high prevalence of breast lumps and breast cancer [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%